A change of normative position: Determining the contours of culpability in criminal law - Ashworth, A (2008)
The purpose of this article is to consider possible justifications for holding a person who intentionally attacks another criminally liable for further unintended consequences that result from the attack. The focus is on the views of John Gardner and on the notion of "change of normative position" as a justification for such additional liability. It is argued that neither the purported justification nor the limiting principles sometimes attached to it are convincing reasons for enhanced liability. © 2008 by the Regents of the University of California. All rights reserved.